2017
DOI: 10.1186/s13287-017-0710-3
|View full text |Cite
|
Sign up to set email alerts
|

Safety and tolerability of intradiscal implantation of combined autologous adipose-derived mesenchymal stem cells and hyaluronic acid in patients with chronic discogenic low back pain: 1-year follow-up of a phase I study

Abstract: BackgroundAdipose tissue-derived mesenchymal stem cells (AT-MSCs) offer potential as a therapeutic option for chronic discogenic low back pain (LBP) because of their immunomodulatory functions and capacity for cartilage differentiation. The goal of this study was to assess the safety and tolerability of a single intradiscal implantation of combined AT-MSCs and hyaluronic acid (HA) derivative in patients with chronic discogenic LBP.MethodsWe performed a single-arm phase I clinical trial with a 12-month follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
208
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(212 citation statements)
references
References 41 publications
2
208
0
2
Order By: Relevance
“…These findings have prompted clinical trials evaluating the safety and efficacy of intradiscal administration of MSCs to attenuate progression of IVD degeneration. These trials have yielded improved pain and functional outcomes in patients with Pfirrmann grade II‐V IVD degeneration . However, identification of an MSC source which demonstrates optimal therapeutic outcomes within the complex pathological environment of the IVD has yet to be defined …”
mentioning
confidence: 99%
“…These findings have prompted clinical trials evaluating the safety and efficacy of intradiscal administration of MSCs to attenuate progression of IVD degeneration. These trials have yielded improved pain and functional outcomes in patients with Pfirrmann grade II‐V IVD degeneration . However, identification of an MSC source which demonstrates optimal therapeutic outcomes within the complex pathological environment of the IVD has yet to be defined …”
mentioning
confidence: 99%
“…One recent study by Centeno et al examined percutaneous injection of MSCs into in vivo human lumbar discs with hernation of the NP; they described a low complication rate, clinical improvement and decrease in the size of disc herniation on long term follow up . When looking at intradiscal injection of MSCs and hyaluronic acid scaffold in a clinical trial of 10 patients, Kumar et al reported no adverse events and improved clinical outcome measures . Of the improved patients, 50% had increased water content within the disc at long‐term follow up, though no changes were noted in radiographic measures of disc degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…(121,122) With regards to MSC therapy, feasibility and safety have been suggested in pilot clinical studies among chronic back pain patients. (123)(124)(125) Analgesic effect, functional improvement, and increased water content by MSC injection therapy have also been reported, although there was no effect on recovering disc height. (123)(124)(125) Furthermore, improvement may be restricted to a group of responders.…”
Section: Regenerative Medicinementioning
confidence: 99%
“…(123)(124)(125) Analgesic effect, functional improvement, and increased water content by MSC injection therapy have also been reported, although there was no effect on recovering disc height. (123)(124)(125) Furthermore, improvement may be restricted to a group of responders. (124,125) Optimization of indication (to distinguish responders and nonresponders), cellsource, cell concentration, and scaffold type are needed, as are larger-scale clinical trials to show long-term safety and efficacy.…”
Section: Regenerative Medicinementioning
confidence: 99%